Levels and clinical significance of the m6A methyltransferase METTL14 in patients with coronary heart disease - Guo, Fengxia; He, Mei; Hu, Bing; Li, Gang (Frontiers in Cardiovascular Medicine, 2023)
Objective To investigate the association of methyltransferase-like protein 14 (METTL14) expression with coronary heart disease (CHD). Methods Three hundred and sixteen patients who attended Henan Provincial People's Hospital between June 2019 and February 2021 with principal symptoms of pain or tightness in the chest and who underwent coronary angiography for definitive diagnosis were enrolled. The uric acid, TG, TC, LDL-C, HDL-C, apolipoprotein A1, free fatty acid, lipoprotein a, homocysteine, CRP, and SAA levels were examined. The levels of METTL14, TNF-α, MCP-1, VCAM-1, ICAM-1, and IL-6 were evaluated by ELISA. Results Patients with CHD had significantly higher m6A methyltransferase activity. In addition, the incidence of diabetes and hypertension, as well as the concentrations of TC, CRP, and SAA were higher in CHD patients. Patients with coronary lesion branches also had significantly increased TG, LDL-C, CRP, and SAA levels. TNF-α, MCP-1, VCAM-1, ICAM-1, and IL-6 expression was also markedly increased in the CHD group (P < 0.001) as was the expression of METTL14 (P < 0.001). The METTL14 expression levels also differed significantly in relation to the number of branches with lesions (P < 0.01) and were correlated with SAA, VCAM-1, ICAM-1, IL-6, and the Gensini score. ROC curve analyses of METTL14 in CHD indicated an AUC of 0.881 (0.679, 0.894) with a cut-off value of 342.37, a sensitivity of 77%, and a specificity of 84%. MCP-1, VCAM-1, IL-6, SAA, and METTL14 were found to independently predict CHD risk. Conclusions METTL14 levels were found to be positively associated with inflammatory markers and to be an independent predictor of CHD risk.